UMPSA Lake attracts anglers for UMPSAs 21st Anniversary Celebration - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 14 October 2023 - The lake at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) in Pekan became a focal point for anglers as over 200 people, along with their families, gathered for a Fishing Competition in conjunction with UMPSA's 21st Anniversary Celebration and in anticipation of UMPSA's 18th Convocation Ceremony to be held from 21st to 24th October.